2008
DOI: 10.1097/tp.0b013e31818aa536
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Human Mesenchymal Stem Cells to Tacrolimus, Mycophenolic Acid, and Rapamycin

Abstract: This study demonstrates that therapeutic concentrations of immunosuppressive drugs affect MSC function. MSC affect the efficacy of immunosuppressive medication. These findings are important for potential clinical use of MSC in combination with immunosuppressants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
64
1
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 32 publications
6
64
1
4
Order By: Relevance
“…However, little understanding exists about how these drugs interact with MSCs. Some studies have demonstrated that therapeutic concentrations of some immunosuppressive drugs affect MSC proliferation and survival [31][32][33]. This study adds new insight to this complex picture.…”
Section: Discussionmentioning
confidence: 90%
“…However, little understanding exists about how these drugs interact with MSCs. Some studies have demonstrated that therapeutic concentrations of some immunosuppressive drugs affect MSC proliferation and survival [31][32][33]. This study adds new insight to this complex picture.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, a high dose of tacrolimus seems to be toxic for MSCs, while MPA and rapamycin at a therapeutic dose just inhibit MSC proliferation [32]. Furthermore, it has been demonstrated that MPA and MSCs have a synergistic immunosuppressive effect [32]. In vivo, MPA and MSCs also synergize to promote long-term allograft tolerance in rat heart transplantation [33].…”
Section: Discussionmentioning
confidence: 99%
“…No difference could be detected between the MSC and control groups on graft rejection episodes, opportunistic infection rates, graft histology Such an effect has not been found with mycophenolic acid (MPA), an MMF metabolite. Moreover, a high dose of tacrolimus seems to be toxic for MSCs, while MPA and rapamycin at a therapeutic dose just inhibit MSC proliferation [32]. Furthermore, it has been demonstrated that MPA and MSCs have a synergistic immunosuppressive effect [32].…”
Section: Discussionmentioning
confidence: 99%
“…At same time, MSC are able to reduce the efficacy of tacrolimus and rapamycin [59,60]. As MSC lack expression of the CTLA-4 ligands CD80 and CD86, it was not surprising that belatacept did not diminish MSC function [62].…”
Section: Cd28mentioning
confidence: 99%
“…Co-administration of MSC with other immunosuppressive drugs is not always encouraged; agents such as tacrolimus, mammalian target of rapamycin (mTor) inhibitor rapamycin and rabbit anti-thymocyte globulin (rATG) negatively affect the suppressive capacity of MSC in vitro [59][60][61]. At same time, MSC are able to reduce the efficacy of tacrolimus and rapamycin [59,60].…”
Section: Cd28mentioning
confidence: 99%